A potential Human Rights Act in Queensland and inclusion of the right to health - Claire E. Brolan; Lisa Herron; Anna Carney; Eva M. Fritz; Judy James; Miranda Margetts (Elsevier, 2018)
Abstract Objective: To identify the level of public support for a Human Rights Act for Queensland (HRAQ) and for inclusion of the right to health by participants in a public inquiry process. Methods: We reviewed the 492 written submissions to the Legal Affairs and Community Safety Committee's Inquiry into a potential HRAQ and the transcripts documenting the public hearings held by the Committee in 2016. Results: A total of 465 written submissions were analysed; 419 (90%) were for a HRAQ. More than 80% of the 'for' submissions advocated the right to health's inclusion. At the seven public hearings, 72 persons made verbal submissions and most supported a HRAQ. Five major themes were identified in our synthesis of the public hearing transcripts. Three related specifically to health and human rights: 1) the need to consider the holistic health and human rights of Indigenous Queenslanders and Indigenous Queensland communities; 2) instilling a human rights culture in Queensland; and 3) access to health care and the underlying determinants of health. The other two themes related to the conduct of the Inquiry: 4) the importance of community participation in developing a HRAQ; and 5) concerns about the public consultation processes. Conclusion: This study found strong support in the majority of submissions for the Queensland Parliament to draft and enact a HRAQ, and for the inclusion of the right to health in such legislation. Implications for public health: The Queensland Parliament's enactment of a HRAQ that expressly included the right to health would increase the accountability and transparency of government health (and related) decision making and resource allocation, and would better identify and address health inequities across the state. This Act is imperative for improving the health and wellbeing of all Queenslanders, particularly rural and remote and Aboriginal and Torres Strait Islander Queenslanders.